A oralidade nas aulas de língua portuguesa na escola básica: um estudo a partir das crenças de professoras da rede pública estadual de Santa Maria/RS - Vitorino, Luane Guerra (2024)
Linked to the Graduate Program in Letters (PPGL), at the Federal University of Santa Maria (UFSM), to the Text Studies and Linguistic Practices research line and to the Oral and Written Genres research group — theory and teaching (GOE), this research aims to investigate, through semi-structured interviews, the beliefs expressed by teachers about the teaching and learning process of the Portuguese language, in basic education. The theoretical contribution is based on Soares (2002), about the history of the Portuguese language in Brazil. With regard to teacher training and the supremacy of grammar and writing, we base ourselves, above all, on Rodrigues (2001), Sacramento (2011) and Travaglia (2002). On the concept of beliefs, especially of teachers, we base ourselves on Barcelos (2002). Regarding studies on orality and oral genres, we are anchored in Travaglia (2017), Bentes (2010), Dolz and Schneuwly (2004), Bueno (2015) and Magalhães (2023). The research methodology is of a qualitative nature, based on semi-structured interviews with eight Portuguese language teachers, from the state public network in the municipality of Santa Maria/RS. Thus, the Portuguese language teachers, at primary and secondary level, answered thirteen questions about Portuguese language teaching in the school context, based on themes such as: reading, grammar, textual genres, oral genres and teacher training. The teachers were divided into two groups. The first four interviewees are more experienced teachers, with more than 25 years of work. In the second group, there are four recently graduated professionals, with less than five years of teaching. In order to better manage the corpus, the interviews were recorded and transcribed, based on theorists such as Marcuschi (2001) and Preti (2009). As partial results, we highlight that some beliefs, such as the relevance of grammar, are different for more experienced teachers than for the group of more recent professionals. We also showed that, in some cases, beliefs change over time.